Exploration of Healthy Diet and its Impact on the Concentration of Learning of Madrasah Ibtidaiyah Teacher Education Students (PGMI) - Anisa Setia Amelia; Delmira Putri; Elvina Desriyanti; Muhammad Hendrizal; Sakinah; Syahrul Khairati (Penerbit Hellow Pustaka, 2024)
This study explores the relationship between healthy eating patterns and their impact on the PGMI ( Pendidikan Guru Madrasah Ibtidaiyah) program at Universitas Islam Negeri Sultan Syarif Kasim Riau. The research employs a qualitative approach through in depth interviews to gain a comprehensive understanding of student’s eating habits and their effects on academic performance. Data were collected over three weeks, focusing on student’s experiences and perceptions regarding nutrition. The findings reveal that many students prioritize cost over nutritional value, often opting for fast food and processed meals, which negatively affects their physical and mental health. Additionally, the study highlights the influence of social and cultural environments on student’s dietary choices, indicating that peer behavior significantly impacts eating habits. Results show that students who maintain a balance diet and regular meal times report improved concentration and cognitive function. The study concludes that promoting healthy eating environments on campus is essential for enhancing students’ awareness and practices regarding nutrition, ultimately contributing to better academic performance. Recommendation for educational institutions to implement programs supporting students’ health and well-being are also discussed.